Characterization of Silicon Carbide Low-Voltage n/p-Channel MOSFETs at High Temperatures - Hui Wang; Pengyu Lai; Affan Abbasi; Md Maksudul Hossain; Asif Faruque; H. Alan Mantooth; Zhong Chen (IEEE Journal of the Electron Devices Society)
SiC-based n-channel and p-channel MOSFETs fabricated by Fraunhofer IISB SiC CMOS technology are characterized from room temperature up to 300°C. The behaviors of these low voltage devices including the short-channel effect (SCE), p-type ohmic contact with high resistivity, and the low channel mobility due to the SiC/SiO2 interface are presented. A thorough analysis is performed to understand the cause of low channel mobility, with TCAD simulations specifically on p-channel MOSFET, providing an insight into the impact of channel length, interface traps, and contact resistivity on device performance. The analysis in this paper is important in the comprehension of the low-voltage SiC MOSFETs so as to achieve balanced n-channel and p-channel MOSFETs and lead to the monolithic integration of SiC ICs with SiC power devices.